(untitled) (Iraqi Journal of Medical Sciences, 2025)
Background: Vaccine development is not an easy task but is a top priority to restore normalcy for Coronavirus-19 disease (COVID-19) and achieve the herd immunity. Objective: To compare the level and duration of humeral versus cellular immune response in vaccinated individuals at one and 8 months after second dose of three different vaccines to severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2), namely Pfizer, AstraZeneca, and Sinopharm vaccines. Methods: The level of neutralizing antibodies and the peripheral mononuclear cells proliferation (PBMC) activity and in vitro IFN-? release by the S1 spike protein-stimulated T cells were monitored using isotype- and species- free competitive blocking ELISA, microculture tetrazolium assay (MTT) proliferation assay and an ELISA technique for the assessment of IFN-? level in a cell culture supernatant, respectively. Results: PBMC proliferation percentage and the concentration of the in vitro IFN-? release were remarkably higher in 8 months than in 1-month post-2nd dose vaccination groups of the three vaccines studied in this study (P